Development of learning media based on the class safari website (microsite) on the material i love the environment around grade 1 elementary school students - Hermawati, Desi; Sumarmi, Sumarmi; Mardhatillah, Mardhatillah; Dewi, Radeni Sukma Indra; Arifin , Slamet (Universitas Kanjuruhan Malang, 2025)
This study aims to develop a microsite-based learning media on the topic